2020
DOI: 10.3390/cells9061546
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Regulates Nerve/Glial Antigen (NG)2-Mediated Angiogenic Activity of Human Pericytes

Abstract: Protein kinase CK2 is a crucial regulator of endothelial cell proliferation, migration and sprouting during angiogenesis. However, it is still unknown whether this kinase additionally affects the angiogenic activity of other vessel-associated cells. In this study, we investigated the effect of CK2 inhibition on primary human pericytes. We found that CK2 inhibition reduces the expression of nerve/glial antigen (NG)2, a crucial factor which is involved in angiogenic processes. Reporter gene assays revealed a 114… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Recently, we have identified a 114-bp fragment (NG2 p1.2.4.1 ) close to the NG2 start codon as a CK2-dependent active promoter region in human pericytes [ 19 ]. Therefore, we investigated whether the activity of NG2 p1.2.4.1 is also affected by CK2 inhibition in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have identified a 114-bp fragment (NG2 p1.2.4.1 ) close to the NG2 start codon as a CK2-dependent active promoter region in human pericytes [ 19 ]. Therefore, we investigated whether the activity of NG2 p1.2.4.1 is also affected by CK2 inhibition in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that NG2 is not only involved in tumor cell proliferation but also in angiogenesis. We previously found that CK2 inhibition reduces the NG2-dependent angiogenic activity of human pericytes [ 19 ]. Therefore, we suggest that CX-4945 is a promising compound for the treatment of NG2-positive GBM, because it targets both the vascular and tumor compartment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spheroid sprouting assay was performed as described previously ( 33 ). The methylcellulose solution was prepared by dissolving 6 g of methylcellulose (sigma) into 250 ml of prewarmed serum free medium, and 250 ml of DMEM containing 10% serum was added.…”
Section: Methodsmentioning
confidence: 99%